Application of starch manioc coating and calcium lactate in fresh-cut of papaya (Research, Society and Development, 2021)
Papaya after minimal processing may present some physicochemical and biochemical changes in response to processing. However, some post-harvest techniques, such as the use of edible toppings and the use of calcium lactate, can be used in order to minimize these changes and prolong the shelf life of the product. This study aimed to verify the efficiency of the application of calcium lactate (6%) and cassava starch-based edible coating (3%) in maintaining the firmness and quality of fresh-cut papaya. Every 4 days, samples were taken for analysis of mass loss, color, pH, total titratable acidity, total soluble solids, ascorbic acid content and firmness (N). It was found that from the 8th day, the vitamin C contents of freshly processed papaya were lower in samples treated with calcium or coated when compared to the control. The use of cassava starch coating was not effective in maintaining the physicochemical characteristics analyzed. It was also found that the minimally processed papaya treated with calcium lactate showed significant maintenance (p